Student partnership: exploring the dynamics in and between different conceptualizations. Issue 12 (2nd December 2021) - Holen, Rasa; Ashwin, Paul; Maassen, Peter; Stensaker, Bjørn
ABSTRACT: The concept of student partnership has attracted increased attention during the last decade, often due to an assumption that it can mitigate neo-liberal agendas and practices in teaching and learning. A review of definitions and understandings of student partnership models shows that most of the research conducted on this topic has been based on normative assumptions, with less focus on how partnership practices play out in different contexts. In this article an analytical framework for analysing student partnership is introduced and tested through an empirical analysis of collaborative practices in centres for teaching excellence in Norwegian higher education. The key findings are that the diversity and dynamics of student partnership depend on the context in which they operate, but more importantly how different practices of partnership play out in parallel in those educational contexts. The result is often a mix of hybrid practices related to different conceptualizations of student partnership.